Combination of NSAIDs with donepezil as multi-target directed ligands for the treatment of Alzheimer's disease. (1st November 2022) - Fang, Lei; Shen, Shiyu; Liu, Qiao; Liu, Zhikun; Zhao, Jian
Graphical abstract: Abstract: To search for multi-target directed ligands for the treatment of Alzheimer's disease (AD), eight hybrid compounds from the combination of non-steroidal anti-inflammatory drugs with donepezil were designed and synthesized. The enzyme test revealed that the synthesized compounds had remarkable inhibitory activity towards both AChE and BChE. The IC50 values of the most active compound 3a reached 0.015 and 0.80 μM for AChE and BChE, respectively, much lower than that of donepezil. Besides, the anti-inflammatory assays showed that the target compounds could effectively inhibit COX-1 and COX-2, and prevent the secretion of proinflammatory cytokines (TNF-α and IL-1β) induced by LPS. Moreover, the target compound could also protect the neuron cells from the damage caused by Aβ42 in vitro. All the results suggest that the hybrid compounds, in particular compound 3a, can be considered as potential candidates for the treatment of AD.